Agility development in youth soccer: the efficacy of fixed-role small-sided games - Neag, I.; Mihaila, I.; Fleancu, L. J.; Stancu, M.; Potop, V.; Barbu, D.; Paun, L.-I.; Mihai, I. (Frontiers in Sports and Active Living, 2025)
Purpose: This study aimed to evaluate the impact of Fixed-Role Small-Sided Games (FRSSGs) on youth soccer players' agility and its components: reaction time, linear speed, and change-of-direction speed (CODS).